Social media platforms, open communication and problem solving in the back-office of Ghanaian extension: A substantive, structural and relational analysis. (May 2021) - Munthali, Nyamwaya; van Paassen, Annemarie; Leeuwis, Cees; Lie, Rico; van Lammeren, Ron; Aguilar-Gallegos, Norman; Oppong-Mensah, Birgitta
Abstract: CONTEXT: Addressing new agricultural challenges may benefit from open communication among field extension agents and other actors who hold relevant expertise, including subject matter specialists and applied researchers. OBJECTIVE: In the context, this article investigates the contribution of two social media messaging platforms, in Ghana, to facilitating open information sharing and interaction amid the emergence of a new pest, fall armyworm. METHODS: Using thematic content analysis and network analysis, we analysed the types of content exchanged over the platforms, the characteristics of the networks in terms of the involvement of different actors in sending and receiving messages; and through platform user surveys established how such interaction patterns were influenced by social relations, self-representational interests and organisational set-ups and rules. RESULTS AND CONCLUSIONS: The results indicate that both social media platforms are characterised by relatively centralised network and communication structures, suggesting that participation in especially sending messages is non-egalitarian. Such structural features are not conducive to complex knowledge and problem solving processes such as knowledge integration and joint problem solving. In line with this, the analysis of the actual knowledge and problem solving processes taking place demonstrated that the platforms were used more for knowledge and information dissemination as well as for the distribution of notifications in support of organisational coordination. Our investigations show that social hierarchies, organisational rules and tactics related to identity management influenced these patterns of interaction and posed constraints to open knowledge and information sharing. Nevertheless, the platforms play meaningful roles in supporting knowledge processes, and are likely to generate useful input for knowledge integration and collaborative problem solving in complementary face-to-face settings. SIGNIFICANCE: The study contributes to an emerging research area that relates social media (other than Facebook) to knowledge sharing, problem solving and broader forms of collaboration in professional spaces, in the African agricultural context. Graphical abstract: Unlabelled Image Highlights: Both platforms' networks are centralised and do not support open communication. Social hierarchies, organisational rules and image management shape the networks. The networks support knowledge sharing, coordination and monitoring activities. Knowledge integration and joint problem solving are not supported by the networks.